CLINICAL AND PROGNOSTIC VALUE OF HYPONATREMIA IN PATIENTS WITH CHRONIC HEART FAILURE - N. T. Vatutin; A. N. Shevelyok; A. N. Zagoruiko (Архивъ внутренней медицины)
The aim: to assess the short-term prognostic value of different types of hyponatremia in patients hospitalized for acute decompensated chronic heart failure. Material and methods. A prospective study included 396 patients hospitalized for acute decompensated chronic heart failure. Hyponatremia was diagnosed in cases of serum sodium level less than 135 mmol/l. The pre-hospital hyponatremia was defined as a decreased serum sodium level on admission, whereas the hospital hyponatremia was referred to cases occurred during hospitalization. In patients with pre-hospital hyponatremia drop of sodium levels ≥ 3 mmol/l during hospitalization was defined as a progressive hyponatraemia. The influence of different types of hyponatremia on the hospital prognosis was determined, while the composite primary endpoint was all-cause mortality and/or transfer to the intensive care unit. Results. Patients with hyponatremia were older and had more severe clinical signs of chronic heart failure, lower left ventricle ejection fraction and higher diastolic dysfunction than normonatremic patients. After adjustment for age, comorbidity and severity of chronic heart failure in Cox regression models hyponatremia was an independent predictor of all-cause mortality and transfer to the intensive care unit (odds ratio 3.1; p < 0.05). Pre-hospital hyponatremia had a higher prognostic value on outcome compared with hospital hyponartemia  (odds ratio 3.9 versus 2.9, respectively; p < 0.05). Progressive hyponatremia was associated with a marked increase of mortality and transfer to the intensive care unit (odds ratio 6.8; p < 0.05). Conclusion. Pre-hospital and hospital hyponatremia are independent predictors for short-term outcomes in patients hospitalized for acute decompensated chronic heart failure. Progression of the pre-hospital hyponatremia is associated with significantly increase of all-cause mortality and risk of transfer to the intensive care unit.